2016
DOI: 10.1038/pr.2016.271
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic hypothermia modulates complement factor C3a and C5a levels in a rat model of hypoxic ischemic encephalopathy

Abstract: HT is associated with significant alteration of complement effectors and their cognate receptors. Complement modulation may improve outcomes in neonatal HIE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 40 publications
3
27
1
Order By: Relevance
“…The decrease in C5a levels may lead to worsened disease outcome as C5-deficient mice demonstrate impaired bacterial clearance (52) and a study of adult patients with sepsis-induced brain dysfunction revealed a correlation between decreased C5a levels with increased mortality (53). Neonatal rats demonstrate elevated expression of C5a and C5 receptors in the blood and brain following HI, which is reduced with therapeutic hypothermia, suggesting that C5a has an injurious effect in cerebral tissue (18,19). In contrast, even though C5 receptor expression was increased in the liver, we did not find any major changes in the mRNA expression of C5 or C5 receptors in the brain of infected mice prior to HI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The decrease in C5a levels may lead to worsened disease outcome as C5-deficient mice demonstrate impaired bacterial clearance (52) and a study of adult patients with sepsis-induced brain dysfunction revealed a correlation between decreased C5a levels with increased mortality (53). Neonatal rats demonstrate elevated expression of C5a and C5 receptors in the blood and brain following HI, which is reduced with therapeutic hypothermia, suggesting that C5a has an injurious effect in cerebral tissue (18,19). In contrast, even though C5 receptor expression was increased in the liver, we did not find any major changes in the mRNA expression of C5 or C5 receptors in the brain of infected mice prior to HI.…”
Section: Discussionmentioning
confidence: 99%
“…at 24 h [F (1,17) = 36.84, p < 0.0001] and 5 d [F (1,19) = 7.20, p = 0.01]. Compared to their respective saline cohorts, brain CCL2 concentrations in infected mice at 24 h were significantly higher in both males and females (18.2-fold in males, p = 0.007; 16.4-fold in females, p = 0.001) (Figure 6A).…”
Section: S Epidermidis Induced Cytokine and Chemokine Production In mentioning
confidence: 99%
See 1 more Smart Citation
“…The neuroprotection observed in Phase 3 of this study using T2 MRI at 7 days after HI was significantly greater than the initial protection observed at 3 h. This suggests that the additional 3 h of hypothermia after imaging at 3 h may improve neuroprotection, and/or that some of the neuroprotective effects of hypothermia may involve later mechanisms of injury such as inflammation. In neonatal rat HIE models, hypothermia reduces caspase-3 activation, apoptosis, and necrosis examined 24 h after HI ( 45 ), modifies complement factor expression ( 46 ), and reduces IL1β levels ( 47 ). Later effects of hypothermia on cytokine levels and microglial activation have been reported in an adult murine stroke model ( 48 ), and a shift in microglial polarization toward an M2 phenotype at 24 h has been observed after hypothermia in an adult rat TBI model ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal hypoxic-ischemic brain damage (NHIBD) is a severe disease that can cause irreversible neurological sequelae, such as cerebral palsy, mental deficiency, memory impairment and learning disabilities and is often characterized by permanent neurological deficits [1,2]. Currently, there is no effective clinical treatment for NHIBD [3][4][5]. Thus, effective therapeutic agents that inhibit damage cascades activated after NHIBD should be identified.…”
Section: Introductionmentioning
confidence: 99%